P151 Assessing the use of the ISBAR3 handover framework in an irish paediatric hospital: a medical student perspective. (June 2019) - Doolan, Aoife; Shiel, James Charles; Williams, Patrick; Hussain, Mohammad; Corcoran, Gearoid; Tan, Joy; Nicholson, Alf
Abstract : Intro: Medical staff are routinely educated on the ISBAR3 framework for clinical handover. This tool is implemented to encourage safer and more effective task transfer during clinical emergencies, referral to other specialties, transfer of hospital and wards. Project aims: To evaluate the use of ISBAR3 during clinical handover in a busy children's hospital To increase awareness of the usage of ISBAR3 as a tool of communication among physicians and healthcare professionals. To promote use of a structured handover framework amongst medical students. Methods: This is a prospective study. A team of medical students attended the morning handover meeting over a period of five weeks, and collected data on the use of ISBAR3. Points were allocated for each component of the framework that was addressed. All data was completely anonymised. The data was then compiled and analysed. We included all patients that were admitted through the Emergency Department; excluded from the dataset were all surgical patients, and patients transferred from other clinical centres. Result: A total of 39 admissions were handed over during the duration of the study. Of these, only one handover fulfilled all elements of the ISBAR3 framework. Parameters were omitted in each of the 38 other cases. The three criteria fulfilled most frequently were: Name, Age and Presenting Complaint and scoring 97%, 89%, 97% respectively. The three most commonly omitted aspects were from the R3 (RISK) of the ISBAR3. This includes : Infection Control, Child Protection, Safety for Discharge, and Infection Control, scoring 10.2%, 7.7%, and 7.6%, respectively. Conclusion: It is clear that the ISBAR3 tool is not being routinely utilised in handover meetings. The impact these findings have on patient care cannot be directly evaluated. Notably, 'Risk' the most commonly omitted parameter. Hence, we have identified an area of clinical practice with scope for improvement. We plan to re-audit this area, following dissemination of information, in order to complete the audit cycle.